(untitled) (Fiep Bulletin - online, 2016)
Introduction: This paper is the result of reflections on the role of blacks in Brazilian society and how is demand or not return for services rendered. And as the focus of this study seek to understand the extent to which politics promote or impede the fight against social inequalities. To analyze both the Law 10639/03. This changing provisions of Law of Guidelines and Bases of National Education, which made compulsory the teaching of History and Afro-Brazilian Culture in schools of basic education and establishing the date of November 20, the school calendar, as awareness day black (SANTOS AND MARTINS, 2012). Objectives: To interpret Article 26-A and 79-B of the law 10639/03 and understand the challenges of managing before this change. Methodology: A survey of school principals Monte Santo de Minas for this work, are you adding the reflections made in the Post School management was made. Results: The managers mostly have demonstrated little knowledge of the law. With changes in the LDB by Law 10639/03 are tools to overcome racial and social inequalities. All claims to bring in its core the search for real equality and human emancipation should be incorporated in the struggle to build new social relationships (ROCHA, 2006). Given the fact that the school is the depiction of society, it is up to the manager becomes aware of the law to make everyone become aware of the law.Conclusion: The need to inform managers and educators of the importance of Law 10639/03 for what is actually being put into practice in schools.